Microstrip Antenna with Mushroom-like EBG for Gain Enhancement at 2.3 GHz Frequency - Wirangga, Tubagus Arya; Milah, Ahmad Saepul; Ismail, Nanang; Ryanu, Harfan Hian (International Conference on Wireless and Telematics (Online), 2024)
This paper proposed a design and realization of microstrip antenna to enhance gain of the antenna using mushroom-like Electromagnetic Band Gap (EBG) method. The operational frequency range for this antenna is 2.35 GHz (2,300 - 2,400 GHz). The designs of two antennas are one without a mushroom-like EBG technique and the other with mushroom-like EBG compared in this working paper, both of the antenna's designs work at the same frequency. Parameters compared are antenna's return loss, VSWR, bandwidth, and radiation pattern. The result is the microstrip antenna using mushroom-like EBG successfully enhanced the gain of the antenna both in simulation and the pabricated antenna. The simulation result show that the microstrip antenna using mushroom-like EBG enhanced the gain by 8,69%, while the pabricated microstrip antenna using mushroom-like EBG successfully enhanced the gain up to 33,15% from 1.849 dBi to 2.462 dBi.